Densidade de estocagem, níveis protéicos e lipídicos da dieta na produção e aceitabilidade do filé de jundiá - Lazzari, Rafael (2008)
This study was conducted to evaluate growth, lipid profile, metabolism and fillet aceitability of jundiá. For this purpose four experiments were conducted in a completely randomly design, where jundiás of the same genetic origin were reared in water re-use system. In the first, it was evaluated four densities (4.2, 6.4, 8.6 and 10.8 kg/m3) in jundiás of both sexes. It was used a total of 420 fish (IW=182.95 ± 2.96 g), that were fed for 120 days until the apparent satiation. It was verified a weight decrease of fish with the increase of the SD used, with elevation of the plasmatic cortisol. In the second experiment, it was tested the sex and dietary protein level influence. In factorial arrangement 2 X 3 (two sexes and three protein levels: 24, 27 and 30% of CP), 270 fish (IW=207.02 ± 26.73 g) were fed controlled during 100 days. The females showed higher growth, with lower protein requirement (24% CP) than that of males (30% CP). These showed higher fillet yield. The increase of the diet protein provided improvement in the fillet lipid profile. Two additional experiments were conducted separately to evaluate the use of soybean oil in the diet (0, 2, 4, 6, 8 e 10% of inclusion, feeding until the satiation). The males (234, IW=193.32 ± 18.78 g 120 days experiment) fed with 8% soybean oil showed better performance. The females (144, IW=237.75 ± 22.35 g 80 days experiment) fed with 10% soybean oil had obtained higher final weight. The feed apparent consumption was higher in males. The higher soybean oil inclusion in the diets decreased the amount of saturated fatty acids and increased polynsaturated fatty acids in jundiá fillets. No differences were detected by the taste panel in the flavor, texture and appearance of the fillets regardeless of fish sex.